A Rare Case Report of an Unusual Dislocation of Fractured Mandibular Condyle. Issue 2 (June 2016) - Mishra, Madan; Singh, Gaurav
Several cases have been reported regarding superolateral, posterior, or superior dislocation of mandibular condyle. The anteromedial dislocation of fractured condyle is the most common among all. This article reports an unusual and unique case of dislocated fractured mandibular condyle wherein the fractured left condylar head was dislocated to the left anatomic angle of mandible. We have not found a single such case in the world English literature published till date. The presented case falls in the rarest of the rare category that will add to our previous knowledge about the types and extent of fracture dislocation of mandibular condyle.